RELATIONSHIP OF DEMOGRAPHY, SOCIO-ECONOMY, AND HUSBAND’S SUPPORT WITH THE USE OF MEDICAL OPERATIVE FOR WOMEN CONTRACEPTIVES (TUBECTOMY) TOWARDS COUPLE OF CHILDBEARING AGE IN PUSKESMAS MOJO SURABAYA - Surya Doni; Lutfi Agus Salim (Universitas Airlangga, 2020)
The family planning program has a very appropriate role in addressing population growth. Most family planning participants chose injections and pills, while medical operative for women contraceptives (tubectomy) and medical operative for men (vasectomy) are the least preferrable. Based on National Board of Population and Family Planning data 2017, the majority of new family planning participants in Indonesia are dominated by family planning participants who use non-long-term contraception methods by 79.48% of all new family planning participants. The use of long-term contraceptive methods from year to year has increased compared to non-long-term contraceptive methods, but there is more interest in acceptors to use non-long-term contraceptive methods. The research objective is to examine the relationship between demographics, socio-economics, husband's support, and the use of medical operative for women contraceptives device (tubectomy). The research type is inferential research with cross-sectional design. The sample in this study was 40 EFAs, of which 20 EFAs used medical operative for women contraceptives (tubectomy), and 20 couples of childbearing age used non-medical operative for women contraceptives (tubectomy). The study results showed that the level of education, age, income, and husbands' motivation are not related to the use of medical operative for women contraceptives (tubectomy). However, the number of children is related to the use of medical operative for women contraceptives (tubectomy). The researcher's suggestion is to conduct education-related for pregnancy management so that the people can estimate the number of children, the distance of pregnancy, and the risk of pregnancy.